PENGARUH STRUKTUR MODAL, PERTUMBUHAN PENJUALAN, DAN BIAYA AGENSI TERHADAP FINANCIAL DISTRESS (STUDI KASUS PADA PERUSAHAAN CONSUMER GOODS SUB INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023) - Vica Fania Praditya Azzahra; Ovi Itsnaini Ulynnuha (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the effect of capital structure, sales growth, and agency costs on financial distress in companies. An unbalanced capital structure can increase the risk of bankruptcy, while stable sales growth has the potential to reduce financial pressure. On the other hand, high agency costs can end the company's financial condition by increasing the conflict of interest between managers and shareholders. The objects of this study are consumer goods companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period, selected using quantitative research methods with multiple linear regression analysis techniques. The sample of this study was 117 companies. The results of the study indicate that capital structure and sales growth have a significant effect on financial distress. The agency cost variable has no effect on financial distress. This study provides encouragement for management in managing financial policies to avoid the risk of bankruptcy.